The Effect Passive and Active Shooting Training on Shooting Accuracy among 12-Year-Old Football Players - Amrullah, Fahrul; Muhaimin, Ali; Lukman, Lukman (LITPAM, 2025)
This study examined the effects of passive and active shooting training on shooting accuracy among 12-year-old football players at Persatuan Sepak Bola Dasan Agung. A quantitative quasi-experimental two-group pretest-posttest design was used. The sample comprised 20 players aged 12 years, divided equally into passive shooting and active shooting groups. Shooting accuracy was assessed through a target-based shooting test from 16.5 meters. Data were analyzed using descriptive statistics, assumption tests, paired-sample t-tests, gain score comparison, correlation analysis, and simple regression. The passive group increased from a mean pretest score of 8.50 to 13.30 at posttest, whereas the active group increased from 5.90 to 11.40. Both groups showed significant within-group improvement. However, the gain score comparison was not significant, t (18) = -0.70, p = 0.493. These findings indicate that both methods improve shooting accuracy, but neither method demonstrated statistically superior effectiveness in this sample. The results provide evidence for combining controlled and dynamic shooting drills in youth coaching.